The dialogue dilemma: the role of patient-clinician communication for low-income people who smoke and manage multiple conditions - Cano, Monique T.; Lindstrom, Michael R.; Muñoz, Ricardo F. (Frontiers in Medicine, 2025)
IntroductionAdults from low-income backgrounds who smoke face significant health disparities related to tobacco use, often at disproportionately high rates. These individuals are more likely to endure multiple mental and physical (MP) health conditions, which can negatively influence their self-rated health (SRH). The quality and effectiveness of patient-clinician communication (PCC) can influence how patients perceive their own health. Understanding how PCC influences SRH among low-income adults who smoke and suffer from multiple MP conditions is essential for clinical care as multimorbidity is on the rise. This study examines how PCC may influence the health perceptions of low-income adults who smoke and have varying MP conditions.MethodsLow-income adults who smoke (N = 58) were recruited from the San Francisco Health Network (SFHN) and were assessed for number of MP conditions, PCC, and SRH. A moderation analysis was performed to examine whether PCC moderated relations between MP conditions and SRH. Follow-up analyses were conducted to examine differences and relationships among variables. In planned exploratory analysis, all possible choices for moderator-independent-dependent-variable selections to explore the best model fit were conducted.ResultsThe results revealed that PCC moderated the association between MP conditions (p < 0.05) and SRH. In follow-up analyses, number of MP conditions predicted poorer SRH for low-income smokers who experienced low (p < 0.001) and average (p < 0.01) levels of PPC but not high levels of PCC. In planned exploratory analysis, based on the Akaike Information Criterion, a quantitative basis for considering SRH as the dependent variable was established.ConclusionThe intersection of tobacco-related disparities among low-income adults who smoke and manage multiple MP conditions is complex. Among this vulnerable population, poor and average PCC adversely influences how patients perceive their own health. Results highlight the importance of quality and effective communication between patients and providers. A culturally informed patient-centered approach to care may improve PCC as it encourages collaborative, individually tailored treatment that empowers patients to actively participate in their own health care.